Rhetoric, Rhetoricians and Poets Studies in Renaissance Poetry and Poetics - Spies, Marijke (Amsterdam University Press, 1999)
The Netherlandish rhetoricians of the sixteenth century have, in the course of the last decades, shed their image of third-rate poets who, lacking all sense of true beauty, were capable only of pompous verbosity and a shallow manipulation of form. The new scholarly assessment has also shed light on the role they played in the cultural and literary life of their time, and it now appears that many of their dramas are well worth staging. Once the sixteenth century was freed from the stigma of being the "preparatory phase" for the Golden Age, the way was clear for thorough studies of the literature produced during the most turbulent period in the history of the Low Countries. This volume contains essays which deal with works written not only in Dutch, but also in French and in New Latin, with topics ranging from the effects of poetic principles on literary practice to the use of poetry as a means for improving society and developing the individual. The unifying thread in these studies is the pivotal importance of rhetoric in all forms of literary expression.